Meningkatan Tanggung Jawab Belajar melalui Layanan Bimbingan Kelompok Teknik Self Management - Tejo Asmara (Journal Prakarsa Paedagogia, 2021)
The research aims to see the effectiveness of using group guidance services with self management techniques for increasing learning responsibility on the students of class IX C SMP Negeri 3 Suruh, school year 2019/2020. The type of research is Guidance and Counseling Action Research. The procedures being used in the research are planning, acting, observing and reflecting. It consits of two cyles. Collecting data techniques being used are: questionnaire, observation and documentation. The result of the research shows that group guidance services with self management techniques improving learning responsibility, from average score 4.0 (low) to score 6.2 (high). Students become more responsible for learning in class, at school and during self study. It can be concluded that group guidance services with self management techniques improving learning responsibility of students.